Pertanggungjawaban Notaris terhadap Akta Otentik yang Dibuat Dihadapannya: Studi Kasus Putusan Nomor 247/Pdt.G/2021/Pn Ckr - Suparman, Maman; Sudirman, Dodi (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2024)
Notaries in carrying out their duties and responsibilities are required to always apply the principle of caution, this is intended so that notaries can provide the best service to the public, and also notaries who do not apply the principle of caution can be subject to sanctions. The large number of notaries makes the competition among notaries increasingly tight and sometimes makes notaries less careful in carrying out their profession. Therefore, the emergence of this journal as an effort to discuss the main issue, namely how the accountability of a Notary towards authentic deeds made by or in front of them. The type of research used in this study is normative juridical, which is a research method by examining and analyzing secondary data. The research results show that authentic deeds as products of Notaries have very strong legal force as evidence in court, therefore the preparation of authentic deeds must be accountable if there are errors in their writing. Thus, the making of authentic deeds must be accountable.